Infrastructure and well-being: employment effects of Jamuna bridge in Bangladesh. Issue 3 (3rd July 2018) - Mahmud, Minhaj; Sawada, Yasuyuki
ABSTRACT: We evaluate the impact of the Jamuna multipurpose bridge, the largest physical infrastructure in Bangladesh, on employment opportunities. We particularly focus on labour market integration effects using survey data that provide information on current and retrospective assessments of household situation in two adjacent districts connected by the bridge. Using a quasiexperimental framework of the canonical difference-in-difference regression methodology, we analyse the impact of this infrastructure on employment and job transition patterns. We find that, along with decreasing household unemployment, the bridge construction facilitated farm-to nonfarm shift of employments. Also, the treatment effects are heterogeneous across age groups.